2013
DOI: 10.1016/j.hrthm.2013.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Acute regional left atrial ischemia causes acceleration of atrial drivers during atrial fibrillation

Abstract: Background The mechanisms by which acute left atrial ischemia (LAI) leads to AF initiation and perpetuation remain unclear. Methods and Results LAI (90-minute ischemia) was obtained in isolated sheep hearts by selectively perfusing microspheres into the left anterior atrial artery. Two CCD cameras and several bipolar electrodes enabled recording from multiple atrial locations: with a dual-camera set-up (Protocol 1, n=10; and 1′, n=4; for bi-atrial or atrio-ventricular camera set-ups respectively), in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Previous studies reported the proposed mechanisms of CAD evoking AF . The presence of CAD can cause myocardial ischemia, resulting in impaired relaxation of the left ventricle and leading to higher pressures in the left atrium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported the proposed mechanisms of CAD evoking AF . The presence of CAD can cause myocardial ischemia, resulting in impaired relaxation of the left ventricle and leading to higher pressures in the left atrium.…”
Section: Discussionmentioning
confidence: 99%
“…High left atrial pressures cause ultrastructural and electrical changes in the atrial tissue, potentially forming the arrhythmogenic substrate for AF . Furthermore, the atrial ischemia/infarction resulted in greater atrial electrophysiological changes and propensity for AF forming the dominant substrate for AF . Systemic inflammation and oxidative stress have contributed to atrial remodeling, and the initiation and recurrence of AF .…”
Section: Discussionmentioning
confidence: 99%
“…Recorded optical movies were processed using custom software based on PV-WAVE (Precision Visuals — Workstation Analysis and Visualization Environment, Visual Numerics Inc.) ( 64 , 65 ). The background fluorescence was subtracted from each frame, and spatial (5 × 5 pixels) and temporal (9 frames) conical convolution filters were used to increase signal-to-noise ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Phase movies and phase singularity locations were obtained after Hilbert transformation of the fluorescent signal ( 66 ). Rotational activity of at least 1 cycle was classified as a rotor ( 64 ).…”
Section: Methodsmentioning
confidence: 99%
“…When these small re-entrant circuits are situated within the atrial wall they may appear as repetitive breakthroughs. 110,111 Rotors have been observed in experimental studies in isolated sheep hearts and were originally visualized with optical mapping. [112][113][114] Based on such studies it has been proposed that rotors are sources of high frequency that thereby drive AF.…”
Section: E Rnakalant Induced Cycle L Ength Prolongationmentioning
confidence: 99%